Anal polyp - Raghav Bansal; Uday Shankar; Ayesha Ain; Joshua Aron; Aaron Walfish (Clinical Case Reports, 2022)
Our case accurately describes a not infrequent finding that is not well understood by endoscopists. Fibroepithelial polyps are benign and should be considered in the differential diagnosis of anorectal polyp.